2018
DOI: 10.1002/ps.5188
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in honey bee gut microorganisms caused by Nosema spp. and pest control methods

Abstract: Our results show that pests such as Nosema spp. and pest control methods alter the composition of bee gut microorganisms, which may have severe consequences for pathogen defense, physiology and general honey bee health. In addition, L. plantarum has potential as a biocontrol agent against Nosema spp. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 65 publications
(76 reference statements)
0
21
0
Order By: Relevance
“…This composition of the microbial community can be used as an indicator of the biological health of the insect. Diaz et al found a negative effect of imidacloprid insecticide on the composition of the microbial community of the intestines of bees [94]. Gram-positive and Gram-negative biomarkers were affected, whereas fungal biomarkers were unaffected.…”
Section: Microbiome Of Bumblebees and Honey Bees And The Impact Of Pementioning
confidence: 99%
“…This composition of the microbial community can be used as an indicator of the biological health of the insect. Diaz et al found a negative effect of imidacloprid insecticide on the composition of the microbial community of the intestines of bees [94]. Gram-positive and Gram-negative biomarkers were affected, whereas fungal biomarkers were unaffected.…”
Section: Microbiome Of Bumblebees and Honey Bees And The Impact Of Pementioning
confidence: 99%
“…and oxalic acid (against V. destructor ). However, these products are known to reduce the diversity and bacterial abundance of the honeybee gut microbiota [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxalic acid, the main component of Api-Bioxal ® , showed and antibacterial effect against different strains of Lactobacillus spp. [ 43 ]. Thus, normal miticide treatments may negatively affect honey bees, since many Lactobacillus species are linked to honey bee health, inhibiting some potential bacterial pathogens [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%